Identification of QTNs Controlling Seed Protein Content in Soybean Using Multi-Locus Genome-Wide Association Studies - Zhang, Kaixin; Liu, Shulin; Li, Wenbin; Liu, Shiping; Li, Xiyu; Fang, Yanlong; Zhang, Jun; Wang, Yue; Xu, Shichao; Zhang, Jianan; Song, Jie; Qi, Zhongying; et al. (Frontiers in Plant Science, 2018)
Abstract Protein content (PC), one important trait in soybean (Glycine max) breeding, is controlled by multiple genes with relatively small effects. To identify the quantitative trait nucleotides (QTNs) controlling PC, in this study we conducted a multi-locus genome-wide association study (GWAS) for PC in a four-way recombinant inbred line (FW-RIL) population composed of 144 lines. FW-RILs were phenotyped for PC in 20 environments, including four locations over four years with different experimental treatments. In addition, the lines were genotyped using SoySNP660k BeadChip, producing genotype data for 109,676 nonredundant single-nucleotide polymorphisms (SNPs). A total of 129 significant QTNs were identified by five multi-locus GWAS methods. Based on the 22 common QTNs detected by multiple methods or in multiple environments, pathway analysis identified 45 potential candidate genes which are likely involved in protein synthesis and metabolism in soybean seeds. On the basis of the distribution of superior alleles in 29 lines (22 elite lines and 7 inferior lines) and 22 common QTNs, we found that the superior allele percentages were higher in the elite lines and lower in the inferior lines. The superior alleles offer an opportunity for breeding soybeans for high PC via marker-assisted selection (MAS). These findings will contribute to the discovery of the polygenic networks controlling PC in soybean, will help improve our understanding of the genetic regulation of PC, and will be useful for molecular breeding of high-protein soybean varieties.